(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the influence of biological activator on productivity and agronomic traits in common bean culture, in which it was carried out at the State University of Mato Grosso do Sul-UEMS, University Unit of Aquidauana, sector of phytotechnics. The experimental design used was in randomized blocks in split plot schemes with four replications. The plots were composed by the Bokashi, Conventional and witness treatments. And the subplots, with dimensions of 5X3 m composed of the cultivars BRS Pérola, BRS Notável, BRS Campeiro, IAC Milênio and BRS Agreste, from the germplasm bank of Embrapa Arroz e Feijão. The evaluations were carried out in the specific vegetative period for each variable, measuring, number of pods per plant, number of grains / pods, green mass of aerial part and root, dry mass of aerial part and root, leaf analysis to determine nitrogen, phosphorus and potassium, root density and length, active nodules, number of nodules per plant and grain yield. The data were collected and submitted to analysis of variance and the means compared by the Tukey test at 5% probability. All analyzes were performed using Rbio software (Bhering, 2017). With that we observed that the cultivar pearl was superior in the variables of root density and mass of one hundred grains, the conventional treatment was superior to the others for the number of branches, in relation to pests, there was a higher incidence of leafhopper in the cultivar BRS Campeiro. It was observed that it is possible to produce beans in an organic system achieving productivity similar to that obtained in the conventional system.